Civil Society and Sustainable Development around the World: Issues and Academic Notes - Wijaya, Melia (Konsultan Surya Buanan, 2024)
The aim of this study is to provide a deeper understanding of how circular economy practices can be applied in different sectors and industries to the SDGs. The study uses 144 scientific papers from the Scopus Database to conduct systematic reviews as research methodologies. Research results to present relevant information on the role of the circular economy in supporting progress towards the Sustainable Development Goals. The main contribution of this research is to provide an in-depth understanding of the role, strategies and impact of civil society in sustainable development, as well as provide valuable insights for policymakers, practitioners and academics in designing and implementing more effective and inclusive development programmes. The limitation of this research is that the articles used are derived only from the Scopus database.